Systemic arterial hypertension in an urban area of southern Brazil: prevalence and risk factors - Piccini, Roberto Xavier; Victora, Cesar Gomes (Revista de Saúde Pública, 1994)
Knowledge of the prevalence of systemic arterial hypertension and its risk factors can be of great value to health policy and planning activities. A cross-sectional study was carried out in Pelotas, southern Brazil, for the purpose of discovering the prevalence of hypertension and selected risk factors. A representative sample of 1,675 adults were studied. The prevalence of hypertension was of 19.8%. The following variables were significantly associated with hypertension after adjustment for confounding variables: black race, advanced age, low educational level, paternal and maternal history of hypertension, use of additional salt on cooked foods, and obesity. The strong association between social class and hypertension found by bivariant analysis was reduced in the multivariate analysis after adjustment for age, sex and race.